The Effectiveness of Graphic on Product’s Virtual Exhibitions as Learning Media in VCD UC - Quina Reivaldi Limantara (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2022)
One way to convey student ideas and concepts is through exhibitions. We are in a pandemic COVID-19, the Graphic On Product (GOP) course in the Visual Communication Design study program at Universitas Ciputra (VCD UC) Surabaya uses virtual exhibitions as an alternative service so that students can still expose their work, considering it is part of the exam assessment and is a pass requirement. This study aims to find views on the effectiveness of virtual exhibitions as learning media in GOP courses, used for future considerations, including after the COVID-19 pandemic. This study uses qualitative methods through descriptive analysis of the results of data collection from exploration sources. The virtual exhibition of Graphic On Product VCD UC Surabaya is the subject of research in this study. The informants who will be the study are determined using the purposive sampling method. From the results of the interview, it can be concluded that the virtual exhibition in the GOP course runs quite effectively as a learning medium. The exhibition has given students access to appreciation from visitors, but there is no access to negative comments that can be constructive in their next work. In the future, virtual exhibitions are considered to still be able to be carried out, even after the COVID-19 pandemic because they have a wider range of visitors and the use and operation of the gallery is quite easy but adequate gadgets and internet are needed to be able to access virtual exhibitions.